High-frame-rate ultrasound analysis of gastric peristalsis using the peristaltic analyzer: a pilot feasibility study - Han, Li; Li, Tingting; Zhuang, Min; Li, Yuan; He, Chuanshi; Zhang, Zijian; Lu, Man (Frontiers in Bioengineering and Biotechnology, 2025)
BackgroundGastric peristalsis plays a pivotal role in regulating gastric emptying and digestive function. However, current clinical assessments of gastric motility primarily rely on invasive or low-temporal-resolution techniques, which fail to support dynamic, real-time evaluations.MethodsWe innovatively extended the Peristaltic Analyzer (PA)—a high-frame-rate ultrasound technology originally designed for endometrial wave analysis to the assessment of gastric peristalsis. Utilizing submicron displacement tracking and spatiotemporal vector analysis, we conducted real-time visualization and quantitative evaluation of gastric motility in 9 healthy volunteers.ResultsAll participants completed image acquisition and peristaltic tracking. The detected peristaltic waves consistently propagated from the proximal to the distal stomach, with an average propagation speed of 1.99 ± 0.18 mm/s, propagation distance of 3.23 ± 0.33 cm, peristaltic intensity of 4.76 ± 1.52 (relative units), interval of 17.31 ± 0.86 s, and frequency of 3.53 ± 0.19 bpm. Waveforms appeared continuous and rhythmic, with uniform propagation direction and clear spatiotemporal profiles.ConclusionAs the first application of the PA high-frame-rate peristaltic analysis technology to gastric motility assessment, this study demonstrates its strong potential as a non-invasive and real-time tool for early detection, quantitative monitoring, and clinical evaluation of functional gastrointestinal disorders. PA exhibited superior performance in motion detection, directional analysis, and fine-scale displacement measurement. These capabilities highlight its potential as a novel tool for early identification and longitudinal monitoring of functional gastrointestinal disorders, postoperative gastric dysmotility, and diabetic gastroparesis, offering substantial clinical translational value and applicability.